2013
DOI: 10.2478/aoa-2013-0047
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Categorisation Method Using Long-term Measurements

Abstract: Previous studies concerning the categorisation method have been based on short daytime measurements. These studies demonstrated urban-noise stratification in the daytime. Nevertheless, legislation and standards refer to noise estimation throughout the day. This paper presents the first attempt to apply the categorisation method to indicators obtained through long-term measurements. The study was conducted in Plasencia, Extremadura (Spain) which has approximately 41,500 inhabitants. First, we conducted a strati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…The study of the spatial characteristics of sound environment variations help defining interpolation functions. Gozalo et al [101] showed that a stratification of roads based on their functionality was helpful before interpolating sound levels showed similarly, based on a measurement campaign in the city of Plasencia (Spain), that the characteristics of sound level variations follow the categories formed with road functionalities.…”
Section: Optimizing Sensor Locations and Network Deployment (1) Spatimentioning
confidence: 93%
“…The study of the spatial characteristics of sound environment variations help defining interpolation functions. Gozalo et al [101] showed that a stratification of roads based on their functionality was helpful before interpolating sound levels showed similarly, based on a measurement campaign in the city of Plasencia (Spain), that the characteristics of sound level variations follow the categories formed with road functionalities.…”
Section: Optimizing Sensor Locations and Network Deployment (1) Spatimentioning
confidence: 93%
“…El principal objetivo de este estudio fue evaluar la aplicación de un método basado en la estratificación de las vías urbanas atendiendo a su funcionalidad como medio de comunicación entre la ciudad y otras ciudades y entre en las diferentes zonas de la ciudad. Este método denominado "Método de Categorización" ha sido aplicado con éxito en diferentes ciudades europeas (Rey Gozalo et al, 2013a, 2013b, 2014.…”
Section: Objetivosunclassified
“…Además, es importante resaltar que este problema ambiental no sólo afecta a las grandes ciudades, también está presente en las ciudades pequeñas o pueblos (Rey Gozalo et al, 2013a).…”
Section: Introductionunclassified
“…Almost all of the respondents in a recent study regarded road traffic as a major source of noise [5]. Many hospitals are located on roads that experience high volumes of road traffic (e.g., in Curitiva, Brazil [36], Valladolid, Spain [37] or Plasencia, Spain [38]). The external facilities of the hospital are also a source of noise (heating and air conditioning, ventilation ducts, alarms, etc.)…”
Section: Introductionmentioning
confidence: 99%